KEY ISSUES IN EFL AUTONOMOUS LEARNING - Wida Rianti (Journal of English Language and Education, 2017)
This paper provides an overview of key issues for EFL autonomous learning. The purpose is a concise summary of ideas that should support more effective learning and develop independent students. The paper first outlines the nature of autonomous learning, particular in academic contexts, pinpoints the knowledge bases needed for EFL learner autonomy and recognize its advantages. From this foundation, a set of research implications for instruction are noted. These implications, in turn, form the basis for recommended teaching practices that will shape autonomous learning. The article concludes by noting the need for additional research to validate, and to provide new insights into, effective learner autonomy.